Reproductive efficiency of Nelore (Bos indicus) cows submitted to ovulation resynchronization programs - Dias, Mirela Balistrieri (2024)
Early pregnancy in the reproductive season (EB) has many benefits for beef production. The ReBreed21 program is a resynchronization program that allows cows to be reinseminated within a 21-day interval. The aims were to evaluate the reproductive efficiency of Nelore (Bos indicus) cows submitted to resynchronization programs for timed-AI (TAI) and to compare doses of estradiol cypionate (EC; 0.5 vs 1.0 mg) in the Rebreed21 (REB21) program. Primiparous (n = 253) and multiparous (n = 645) cows were randomly assigned to 3 resynchronization groups: conventional (CON; n = 299), REB21 with 0.5 (REB0.5; n = 299) or 1.0 mg (REB1.0; n = 300) of EC. All cows received the same protocol for 1st TAI, starting on d-9 with an intravaginal progesterone device (P4; 0.5 g), 2.0 mg estradiol benzoate (EB), and 0.53 mg cloprostenol sodium (PGF). On d-2, 0.53 mg PGF, 300 IU eCG, and 1.0 mg EC were given, concomitant with P4 removal. On d0, 8.4 μg buserelin acetate (GnRH) was given and TAI was done. On d12, REB21 groups received a P4 device (0.5 g), kept until d19, when 300 IU eCG, 0.5 (REB0.5) or 1.0 mg (REB1.0) EC were given and cows had their tails chalked. On d21, pregnancy diagnosis (PD) was performed in all groups by evaluating the corpus luteum (CL) blood perfusion, and nonpregnant cows in REB21 groups received 8.4 μg GnRH, and 2nd TAI was performed. On d33, PD was confirmed, and those cows in REB21 groups inseminated on d21 were resubmitted to the same REB21 protocol, receiving the 3rd TAI on d42. Those cows diagnosed as pregnant on d21, but nonpregnant on d33 were considered false-positives (FP) and were resubmitted to the same 1st TAI protocol on d33, receiving the 2nd TAI on d42. Thereby, on d42, the last TAI of a 42-d breeding season (BS) was performed. Cows in CON received up to 2 TAI, while cows in the REB21 program received up to 3 TAI. Ultrasound was performed on d54 and 75, to assess PD, FP, and pregnancy losses (PL). After 21d of BS, REB1.0 and REB0.5 had a greater pregnancy rate (PR) than CON (77.7a; 75.6a; 52.8%b). However, final PR did not differ among groups (84.7; 84.9; 79.9%; respectively), although in REB1.0 and REB0.5 the mean time for pregnancy was shorter than in CON (8.5a; 10.8a; 15.8b d, respectively). Expression of estrus was greater for REB1.0 than REB0.5 but PR, FP, and PL did not differ between these groups. Regardless of EC dose, the REB21 program induced greater PR than CON after d1 (59.9 vs 52.8%), d21 (76.6 vs 52.84%), and tended to have a greater pregnancy rate at d42 of the BS (84.8 vs 79.9%). There was a difference in FP (13.7 vs 7.5%) but have not for PL (3.2 vs 3.1%) between CON and REB21 programs. In conclusion, the REB21 program anticipated and tended to increase the number of pregnancies during a 42-d BS. These findings highlight the potential of this super-early resynchronization program to enhance the reproductive efficiency of Nelore cows.